2023
DOI: 10.1186/s12885-023-10692-x
|View full text |Cite
|
Sign up to set email alerts
|

ORGAVADS: establishment of tumor organoids from head and neck squamous cell carcinoma to assess their response to innovative therapies

Abstract: Background Radiotherapy is one of the cornerstones of the treatment of Head and Neck Squamous Cell Carcinomas (HNSCC). However, radioresistance is associated with a high risk of recurrence. To propose strategies (such as combinations with drugs) that could over intrinsic radioresistance, it is crucial to predict the response to treatment. Patient-Derived Tumor Organoids (PDTO) are in vitro tridimensional microtumors obtained from patient’ own cancer samples. They have been shown to serve as rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The TRIPLEX study and this manuscript have been written in accordance with standard protocol items, namely recommendations for interventional trials (SPIRIT). The method and design of this study is based on the ORGAVADS study described by Perréard et al [ 30 ].
Fig.
…”
Section: Method/designmentioning
confidence: 99%
See 2 more Smart Citations
“…The TRIPLEX study and this manuscript have been written in accordance with standard protocol items, namely recommendations for interventional trials (SPIRIT). The method and design of this study is based on the ORGAVADS study described by Perréard et al [ 30 ].
Fig.
…”
Section: Method/designmentioning
confidence: 99%
“…RNA analysis will be performed according to the protocol described in Perréard et al [ 30 ]. Briefly, total RNA will be extracted using the Nucleospin RNA kit (Macherey Nagel, Hoerdt) and libraries will be made with the QuantSeq 3’RNA Library Kitto.…”
Section: Method/designmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Moreover, patient-derived tumoroids from HNC facilitate treatment stratification and serve as an indispensable tool for the validation and identification of biomarkers. 20 Perréard et al (2023) successfully developed organoids from HNSCC to assess their sensitivity to different novel therapeutic approaches and demonstrated that these organoids are reliable surrogates for predicting tumor response in patients. 21…”
Section: Opportunities For Patient-derived Organoid Cultures In Head ...mentioning
confidence: 99%
“…20 Perréard et al (2023) successfully developed organoids from HNSCC to assess their sensitivity to different novel therapeutic approaches and demonstrated that these organoids are reliable surrogates for predicting tumor response in patients. 21…”
Section: Opportunities For Patient-derived Organoid Cultures In Head ...mentioning
confidence: 99%